Solid-state NMR structural investigations of peptide-based nanodiscs and of transmembrane helices in bicellar arrangements. (March 2019) - Salnikov, Evgeniy S.; Aisenbrey, Christopher; Anantharamaiah, G.M.; Bechinger, Burkhard
Highlights: Double-belt arrangement of the rim structure of peptide nanodiscs. Insights into the supramolecular arrangement of HDL. Magnetically oriented DIBMA nanodiscs. Solid-state NMR spectra of a transmembrane domain of the MHC class II receptor. Abstract: The membrane topology of the peptide 18A, a derivative of apolipoprotein A-I, is investigated in structural detail. Apolipoprotein A-I is the dominant protein component of high density lipoproteins with important functions in cholesterol metabolism. 18A (Ac-DWLKA FYDKV AEKLK EAF- NH2 ) was designed to mimic the structure of tandem domains of class A amphipathic helices and has served as a lead peptide for biomedical applications. At low peptide-to-lipid ratios 18A partitions into phosphatidylcholine membranes with helix topologies parallel to the membrane surface, an alignment that is maintained when disc-like bicelles form at higher peptide-to-lipid ratios. Notably, the bicelles interact cooperatively with the magnetic field of the NMR spectrometer, thus the bilayer normal is oriented perpendicular to the magnetic field direction. A set of peptides that totals four 15 N or 2 H labelled positions of 18A allowed the accurate analysis of tilt and azimuthal angles relative to the membrane surface under different conditions. The topology agrees with a double belt arrangement forming a rim that covers the hydrophobic fatty acyl chains of the bicelles. In another set of experiments, it was shown that POPC nanodiscs prepared in the presence of diisobutylene/maleic acid (DIBMA) polymers can also be made to align in the magnetic field. Finally, the transmembrane domains of the DQ alpha-1 and DQ beta-1 subunits of the major histocomptability complex (MHC) class II have been prepared and reconstituted into magnetically oriented bicelles for NMR structural analysis.